Implementación de técnicas difusas para la evaluación de impacto ambiental mediante sistemas de información geográfica - Luque Díaz, Germán Yesid (Universidad Antonio Nariño, 2022)
The present work was carried out with the purpose of applying Fuzzy Techniques with geographic information systems as one methodology for the environmental impacts assessment, having as a case study underground exploitation of auroargentiferous minerals "SOTO NORTE". In the development of this project, an analysis was carried out in which the advantages of using fuzzy techniques over conventional methods are identified and the way in which geographic information systems help to focus on the areas in which the impact is relevant in case of carrying out the construction project.